Vegetative Propagation of Albizia lebbek through Stem Cuttings - Handa, A. K.; Khare, N.; Chauhan, S. P. S. (Indian Forester, 2005)
The present study was conducted during February, 2000 to December, 2002 to standardize the vegetative propagation of Albizia lebbek species through stem cuttings and to study the biochemical changes occurring within the cuttings during different stages of rooting and its overall effect on rooting success of the species. It was observed that IBA was more effective than NAA in inducing rooting in this species and maximum rooting success was achieved at IBA 400 ppm (71.66 %).